Enhancing primary healthcare delivery in Nigeria through the adoption of advanced technologies - Umar, Abbas B.; Sani, Saifuddeen K.; Aliyu, Lukman J.; Hassan, Musa; Imam, Maryam; Haruna, Usman A.; Ibrahim, Adamu M.; Lucero-Prisno III, Don E. (Narra Sains Indonesia, 2024)
Enhancing primary healthcare delivery in Nigeria by adopting advanced technologies holds substantial promise for improving healthcare accessibility, quality, and efficiency. Primary healthcare focuses on community-based, essential care that is practical, socially acceptable, and affordable. Despite efforts to improve healthcare delivery, challenges persist, particularly in rural and underserved areas. The aim of this study was to explore the transformative potential of technologies such as telemedicine, electronic health records (EHRs), health information systems (HIS), artificial intelligence (AI), and medical drones in addressing these challenges. Telemedicine facilitates access to healthcare in remote areas by overcoming geographical barriers. EHRs streamline administrative and clinical processes, enhancing patient care and safety. HIS improves data management, patient safety, and provider communication. AI revolutionizes diagnostics, treatment personalization, and operational efficiency. Medical drones offer innovative solutions for delivering medical supplies to remote locations. The paper also addresses the challenges associated with these technologies, including infrastructure limitations, regulatory issues, and data privacy concerns. Recommendations include investing in infrastructure, developing regulatory frameworks, building capacity, fostering public-private partnerships, engaging communities, and implementing robust data security measures. By addressing these recommendations, Nigeria can leverage advanced technologies to enhance healthcare delivery and achieve better health outcomes.